Perspektif Multinasionality dan Kepemilikan Institusional Terhadap Thin Capitalization Perusahaan Asing - Elok Faiqoh Himmah (LPPM Universitas Informatika dan Bisnis Indonesia, 2020)
This study aims to analyze the thin capitalization that is applied in multinational companies for the effectiveness and efficiency of corporate financing. This study uses independent variables namely multinational and managerial ownership. The study population consisted of all non-financial companies listed on the Indonesia Stock Exchange from 2017-2019. This study takes a sample from multinational companies that are non-financial institutions. This study uses multiple linear regression analysis as a statistical method. The independent variables used in this study are multinational and managerial ownership, then the dependent variable is thin capitalization.